Location strategies of Chinese multinationals - Li, Lin (2021)
The rapid internationalization of Chinese firms has attracted great attention from international business scholars. The different strategies that Chinese MNEs have adopted in the spatial distribution of their economics activities have raised several important questions, i.e. how Chinese multinationals organize their portfolio of locations in foreign markets, and what kind of factors determine the choice of different location portfolio? The main purpose of this study is to investigate the effect of home country environments on location portfolio of Chinese multinationals. This study seeks to elaborate the traditional location theory to combine perspectives from institution-based view and economic geography in examining three dimension of location portfolio: non home-region vs. home-region orientation, developed-country vs. developing-country orientation and OFDI agglomeration at the subnational regions. Using a large sample of Chinese OFDI projects, this study constructs two datasets. One encompasses 28,181 OFDI locations in 139 host countries during 1999-2018 which is used to test the hypothesis regarding non home-region vs home-region orientation, and developed-country vs. developing-country orientation. Another dataset is comprised of 2,728 OFDI projects in 250 subnational regions of 29 foreign countries during 2003-2018, which is used to analyze the effect of OFDI agglomeration. For the first two dimensions of location portfolio, the findings indicate that both state ownership and sino-foreign joint venture have positive effects on non home-region orientation while both stronger institution in (home) subnational region and institutional instability has negative effects on non home-region orientation. Second, the results show that both state ownership and institutional instability have positive impacts on developed-country orientation, while sino-foreign joint venture has negative effects on developed-country orientation. Furthermore, I also find that a greater degree of institutional instability in the home country induce Chinese MNEs to break existing location portfolio and choose a new location. For the OFDI agglomeration, the findings provide strong evidence for both country-of-origin agglomeration and industry-specific agglomeration in OFDI location of Chinese MNEs. The study also finds Chinese MNEs engaged in R&D activities respond more actively to industry-specific agglomeration while Chinese MNEs engaged in production activities are less motivated by industry-specific agglomeration. The results also indicate that Chinese MNEs engaged in R&D, production and supporting service are less motivated by country-of-origin agglomeration while Chinese MNEs undertaken marketing and sales activities are more likely to cluster in country-of-origin agglomeration. Further, the result indicates Chinese state-owned enterprises are less motivated to cluster in country-of-origin agglomeration. I also find that there is a positive relationship between the high degree of industry agglomeration in the home country and the probability of Chinese multinational locating in industry-specific agglomeration in the host country.